Confirmation of conceptual validity of Czech version of group environment questionnaire by structural equation modeling - Prokešová, Eva; Musálek, Martin (Acta Universitatis Carolinae. Kinanthropologica, 2011)
The Group Environment Questionnaire (GEQ) is an instrument intended for the study of cohesion in sport teams. The main aim of this study was to confirm the conceptual validity within the Czech vision of Group Environment Questionnaire by method of structural equation modeling. For translation of the questionnaire was utilized a modified direct translation method. A total of 1169 participants (848 men and 321 women) completed the GEQ. For data analysis we applied a confirmation factor analysis approach. The original model was tested to verify the structural theory and diagnosis quality of this tool. Results showed only average values of models fit RMSEA in Czech condition on the level 0,081 and CFI 0,901 and found poor item loading in fourth factor of diagnostic tool GI-T with factor validity on level 0.216. We assume that for better fit and diagnostics quality it is necessary to repeat the process of content validity and change or restrict the number of items.
Keywords: SEM; Hockey; volejbal; Models, Psychological; explorativní faktorová analýza; Group Structure; statistika jako téma; koheze; fotbal; hokej; Group Processes; GEQ; skupinové procesy; průzkumy a dotazníky; Models, Structural; týmový sport; zjišťování skupinových postojů; Focus Groups; Volleyball; Role; skupinová struktura; lidé; role; psychologické modely; Sports; Humans; konsensus; modely strukturální; Financing, Organized; Consensus; Basketball; Soccer; basketbal; Surveys and Questionnaires; Statistics as Topic; financování organizované; sporty